Acid-sensing ion channels in gastrointestinal function. (July 2015) - Holzer, Peter
Abstract: Gastric acid is of paramount importance for digestion and protection from pathogens but, at the same time, is a threat to the integrity of the mucosa in the upper gastrointestinal tract and may give rise to pain if inflammation or ulceration ensues. Luminal acidity in the colon is determined by lactate production and microbial transformation of carbohydrates to short chain fatty acids as well as formation of ammonia. The pH in the oesophagus, stomach and intestine is surveyed by a network of acid sensors among which acid-sensing ion channels (ASICs) and acid-sensitive members of transient receptor potential ion channels take a special place. In the gut, ASICs (ASIC1, ASIC2, ASIC3) are primarily expressed by the peripheral axons of vagal and spinal afferent neurons and are responsible for distinct proton-gated currents in these neurons. ASICs survey moderate decreases in extracellular pH and through these properties contribute to a protective blood flow increase in the face of mucosal acid challenge. Importantly, experimental studies provide increasing evidence that ASICs contribute to gastric acid hypersensitivity and pain under conditions of gastritis and peptic ulceration but also participate in colonic hypersensitivity to mechanical stimuli (distension) under conditions of irritation that are not necessarily associated with overt inflammation. These functional implications and their upregulation by inflammatory and non-inflammatory pathologies make ASICs potential targets to manage visceral hypersensitivity and pain associated with functional gastrointestinal disorders. This article is part of the Special Issue entitled 'Acid-Sensing Ion Channels in the Nervous System'. Highlights: ASICs in the gut are primarily expressed by sensory neurons. ASICs initiate protective mechanisms in the gut. ASICs can also contribute to gastrointestinal hypersensitivity and pain. ASICs are upregulated by inflammatory and non-inflammatory pathologies. ASICs are potential drug targets in visceral hypersensitivity and pain.